Illicit Alcohol Markets and Everyday Crime: a Historical Reconceptualization - Yeomans, Henry (The British journal of criminology, 2024)
Illicit alcohol markets are widely viewed as exceptional phenomena. Partly in consequence, they are under-researched and have a low political profile in Britain. This article proceeds from a contrary understanding that illicit alcohol markets are actually persistent features of the history of modern Western societies. Based on original archival research, it examines how illicit alcohol markets in England and Wales changed but endured across the long nineteenth century (c.1789-1914). It charts the decline of wholly illegal alcohol markets and the increasing prominence of hybridized enterprises which entwined legal and illegal activities. Importantly, the article proposes a significant new conceptualization of illicit alcohol markets as everyday crimes. It then considers the implications of this argument for criminological research and alcohol policy.